Development of a microarray based telomerase binding assay reveals unusual binding of a cytochalasin derivative - Jia Li Ye; Lu Fan; Christian Bär; Thomas Thum; Oliver Plettenburg; Russell J. Cox; Carsten Zeilinger (Scientific Reports)
Abstract Telomerase reverse transcriptase is crucial for cellular development, regeneration, and disease processes. Strategies for both telomerase activation and inhibition have been intensively explored in the past decades. In this study, we present a highly miniaturized, microarray-based assay designed to identify compounds that target telomerase. The active protein was either recombinantly derived from E. coli or obtained from cell lysates of human cancer cell lines and mouse cells expressing telomerase. Using non-contact spotter technology, these lysates or purified telomerase proteins were transferred onto nitrocellulose pads on a microarray. A telomerase binding assay, incorporating fluorescent labelled primer, the template RNA telomerase RNA component, and fluorescent labelled nucleotide as a primer cocktail, was conducted in incubation chambers. Binding of this primer cocktail to spotted telomerase from cell lysates, and from purified recombinant telomerase resulted in an increase in bound fluorescence. Epigallocatechin gallate, a known telomerase inhibitor, reduced this fluorescence in a dose-dependent manner with micromolar affinity. The inhibitory effect on telomerase was validated by thermophoresis and its impact on activity was shown in a Telomerase Repeated Amplification Protocol (TRAP) assay. Additional screening identified that 4’-iodo cytochalasin H inhibits primer cocktail binding to cell lysate in the low micromolar range. Molecular modeling and docking pinpointed a putative binding site for epigallocatechin gallate in a human telomerase homologue, and a putative binding site for 4’-iodo cytochalasin H. In summary, we developed an assay that can be employed to discover new telomerase inhibitors and that will serve as a valuable tool for screening of activators.